Trends and changes in hydroclimatic variables : links to climate variability and change - Teegavarapu, Ramesh S. V., 1970- (Elsevier, 2019)
"[D]iscusses the change detection and trend analysis methods used to assess hydroclimatic variables in a changing climate. It also assesses changes and trends in hydroclimatic variables using state-of-the-art parametric and nonparametric statistical approaches and evaluates the influences of climate change and variability on spatial and temporal changes in hydroclimatic variables. This book offers a variety of real-life case studies and problem-solving techniques for a field that is rapidly evolving, and highlights methods to evaluate trends, non-homogeneity and points where time-series characteristics change. In addition, it covers the subject of climate variability and change in great detail, including spatial and temporal changes in precipitation, streamflow, and sea levels"--Page 4 of cover